A study of certain Aythya hybrids - Gillham, Eric; Harrison, Jeffery G; Harrison, Jeffery G (Wildfowl, 1966)
Six distinct types of drake Aythya hybrids which may be seen in Britain are described both from museum specimens and as seen in the field. These are the progeny of various combinations of four species: Pochard, Tufted Duck, Ferruginous Duck and Scaup. A description is also given of a drake hybrid between two North American species, the Redhead and Ring-necked Duck. Female Aythya hybrids must often remain unrecognised: four specimens are described. The relatively frequent occurrence of hybrids resembling species rarely found in Britain necessitates very careful scrutiny of all records purporting to be of Lesser Scaup, Ring-necked Duck and Ferruginous Duck.